Improvement of melatonin to the learning and memory impairment induced by amyloid beta-peptide 25 - 35 in elder rats - Shen Yu-Xian; Wei Wei; Yang Jun; Liu Chao; Dong Chen; Xu Shu-Yun (Acta Pharmacologica Sinica, 2016)
Aim: To investigate improvement of melatonin on learning and memory impairment induced by amyloid beta-peptide 25 - 35 (Abeta25-35) in elder rats. Methods: Step-down type passive avoidance test, shuttle-box test, and Morris water maze were used together to determine effects of Abeta25-35 and melatonin on learning and memory. Pathological changes were observed by HE, Congo red, and Ag staining. Results: The elder rats were injected bilaterally Abeta25-35 20 microg into the hippocampus to induce learning and memory dysfunction. Melatonin administration (0.1, 1, and 10 mg/kg, ig x 8 d) to the Abeta25-35-treated rats prolonged the latency, shortened the total stimulating time, and decreased the number of errors in the step-down test. Shuttle-box test showed that melatonin improved amnesic rats' performance at the same doses. Melatonin (0.1, 1, and 10 mg/kg ), giving for 10 d, could enhance the spatial resolution of amnesic rats in Morris water maze test. Also in Abeta25-35-treated group, a decrease in the number of neurons in cortex and hippocampus, a massive glial reaction, and neurophilic phenomenon were detected by HE staining; the positive vascular amyloidosis by Congo red and fibrils by Ag staining were observed. Melatonin (0.1 and 1 mg/kg)could inhibit above pathological changes in Abeta25-35 group. Conclusion: Melatonin improved the impaired learning and memory induced by Abeta25-35 in elder rats.